Hukum Tata Negara Adat Minangkabau dan Aceh dalam Bingkai Negara Kesatuan Republik Indonesia - Hudiana, Raihan (Jurnal Konstitusi & Demokrasi, 2021)
As the state's fundamental law, the constitution is a legal document that regulates the general provisions of reference for making more specific laws and regulations. The birth of a constitution stems from the shared consensus of a nation that contains the distinctive values of its people, including those in Indonesia. Indonesia has various kingdoms with a long history in each region that is part of it, including Aceh and Minangkabau. The condition of the two regions with a long history of civilization has led to customary constitutional law based on prevailing values. The validity of customary law raises questions about its legitimacy, considering that the 1945 Constitution as the state's fundamental law already exists. So, these problems will describe using normative juridical research methods based on favorable regulations and expert opinions. This research produces findings that customary governance law can preserve within the framework of the Unitary State of the Republic of Indonesia (NKRI) through Article 18B of the 1945 Constitution of the Republic of Indonesia, which recognizes its existence. This recognition does not mean that it applies in the aspect of positive law but instead applies as a social institution that exists in society.